Is Canadian Literature Still “National”? Twenty-First-Century Canadian Literature in Spatial Perspective - Milz, Sabine (Studies in Canadian Literature, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Rethinking contemporary Anglo-Canadian literature from a spatial perspective suggests that it is not disappearing as a national literature; it is simply changing shape. Henri Lefebvre’s theory of abstract and absolute space developed in The Production of Space (1974) can be used to frame the concept of national literature in spatial terms. As demonstrated through interviews with active players in the publishing industry in Alberta, Saskatchewan, and Manitoba, Canadian literature is being constituted by such diverse forces as the changing nature of bookselling, the internet, and dwindling funding opportunities, all within the context of neoliberal global capitalism. However, these changes have not fragmented Canadian literature to the point of erosion, as Stephen Henighan and others have suggested. Situated within a market- and consumer-driven cultural, political, and economic landscape shaped by localism and globalism more than by 1970s nationalistic fervour, the space of Canadian literature today is simultaneously centralized and decentralized.